MOSQUES AND THE PROBLEM OF GENDER BIAS - Moh. Faiz Maulana; Windi Susetyo Ningrum (Marwah: Jurnal Perempuan, Agama dan Jender, 2023)
This paper tries to see the relationship between women and the mosque. The mosque, which should be a place that is freely accessible to all Muslims regardless of gender, has so far been dominated by men, both in terms of daily activities (worship) and incidental ones. This paper uses a qualitative method. The data obtained were analyzed and interpreted using the perspective of gender and feminism. As a social space (besides the worship space) the mosque is in fact still gender biased. We can see this from mosque facilities that are less sensitive to the presence of women, for example, the absence of a place for ablution for women, places for women’s prayers that are less representative, and also the structure of mosque management or mosque takmir which is still dominated by men. Of course, this is due to several factors, such as misinterpretation of the role of women, and the lack of gender awareness in mosque management. In fact, we know that besides being a place of worship, mosques are the best space for building social relations, accessing information, and empowering the community.